Assessment of Self-Medication Practice among Nursing and Non-Nursing Undergraduate Students - Elkafafi, Hanan; Shaimaa M. El-Hadary; Hanaa Azmi Saad (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Self-medication practice involves consumption of medicines by one’s own initiative or on the consultation of others without the guidance of a physician. Self-medication and use of over-the-counter drugs are prevalent worldwide public health concerns. University students of medical and nonmedical disciplines may have different levels of health educationAim: study self-medication practice among Nursing and non-Nursing undergraduate students of MTI University Research design: A cross-sectional and correlation designs were used to carry out this study.Setting: the current study was conduct in in faculty of Nursing and faculty of Mass Media at one of the private university in Egypt, Modern University for Technology and Information (MTI).Sample: sample of total 200 students from nursing college and Mass Media College, One hundred were chosen randomly for each college. Tool: self-administered questionnaire was used to collect the data divided to two section, the first section featured questions regarding demographic information, and the second section focused on self-medication and consisted of 9 questions. Results: 90% of nursing students and 60 % of mass media students practice self-medication.  Both group agree about some reasons with no significant difference while there is a statically significant regarding to other reasons. Majority of students in both group get their drug from home pharmacy according to physician advice (98%, 92 % respectively). There was a highly statistical significant association between type of  education, presence of home pharmacy, degree of care about health and current health status and self-medication practice (P value= 0.000).Conclusion: In conclusion, nursing students practice self- medication more often than mass media students. The common reasons behind practicing self-medication according to both groups; they can managing their symptoms, avoiding long waiting time in the clinics, they want having an active role in their health, and their relatives, friends and media empower them to manage symptoms. Their sources for obtaining drugs are pharmacy, home pharmacy, family and friend. Type of education medical or non-medical affect on self-medication practice; while being a first year or last year not affect on self-medication practice.  Recommendations: the study recommended that replicate this study on a larger study sample in different settings to generalize the results and Health professionals have to increase students’ awareness about risk of self-medication practice and its health consequences.